Groundwater Dynamics and Vulnerability Analysis — A Case Study of Xuchang - Wang, Jinjing; Zhang, Wenjia (International Journal of Natural Resources and Environmental Studies, 2025)
In recent years, the quantity and quality of water resources play an increasingly important role in economic development, social progress and people's healthy life, etc. The situation of water resources directly affects the scale of urban development and the development pattern of regional economy. Based on the DRASTIC model assessment, the groundwater dynamics and vulnerability in Xuchang City are analyzed. The results show that the change of shallow groundwater level is consistent with the change of precipitation on the whole, and the groundwater level drops due to the excessive exploitation in successive years. The change of middle and deep groundwater level is mainly affected by artificial exploitation, and the water level decreases year by year. Due to the implementation of mining restrictions around 2000, the shallow and middle deep water levels recovered slightly. The groundwater vulnerability level in Xuchang City is poor to good, and the vulnerability zoning results gradually increase from northwest to southeast, which is related to the lithology and permeability coefficient of the vasses zone.